Implementasi Model Pembelajaran Patriot untuk Mengembangkan Kemampuan Mengelola Usaha Mahasiswa - Naswan Suharsono (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This study was conducted to explore the existence of entrepreneurial learning patterns that can be used to develop students' business management skills through the implementation of the PATROT model after the COVID-19 pandemic. This effort was carried out through the implementation of the PATRIOT model with five online class facilities, an entrepreneurship laboratory, and field observations for the Undiksha Young Entrepreneur Association (YES) group. Field activities are based on the idea that increasing the ability to innovate creatively, the courage to face risks, and turning challenges into opportunities are the basic characteristics that shape the entrepreneurial behavior of college graduates. Learning activities are carried out by integrating activities in the Undikaha e-learning class (synchronous and asynchronous) and through SIPEJAR FE UM. This exploratory research was conducted in 5 classes of FE Undiksha Singaraja students, and 5 classes of partner students of FE UM offering 2020 who took the Entrepreneurship course. Data were obtained through document review and student questionnaires about the effectiveness of learning which were analyzed descriptively according to the characteristics of the information and content analysis according to the message content. The results of the study indicate that there are five components of learning activities that can be integrated or combined to develop the ability to take business actions. The five components are: online information search, learning interaction (synchronous vs asynchronous), job training (group vs independent), assessment (process vs outcome), and feedback and follow-up. The results of the study indicate that the ability to manage a business can be improved through a cooperative mechanism in group work, with the supervisor and project partners. The findings of this study should be continued by testing the effectiveness of learning patterns and scenarios for integrating online work activities, KWU laboratory assignments and business partnerships with practitioners.